IMPLEMENTASI METODE WATERFALL PADA APLIKASI SEWA SAWAH DI DESA TANJUNGSARI KABUPATEN JEMBER BERDASARKAN PERSPEKTIF EKONOMI PEDESAAN - Endra Rahmawati (STMIK YADIKA BANGIL, 2021)
Abstract : This study aims to design a rice field rental application in Tanjungsari Village, Jember Regency which is viewed from the Rural Economic Perspective. This review of the rural economic perspective is carried out by considering the calculation of the profits obtained between rice field owners and rice tenants in developing and cultivating agricultural land. The rice field rental system in force in this village mostly uses an annual payment system, although some use a profit-sharing system and are based on the harvest season. The annual system is widely chosen because its economic value is higher than other rental systems. This is because some crops can be harvested more than once a year as well as the possibility of easy monitoring for some rice field owners who are residents who come from outside the city and own agricultural land in the area, but cannot manage it well. The process of renting rice fields in the village usually takes place conventionally by telephone, coming directly to the house of the rice field owner, or through the services of an intermediary. The making of a written agreement regarding the lease is sometimes ignored, only based on a verbal mutual agreement. To deal with these problems, we need a rice field rental application that is built on a web-based basis using the Waterfall method by focusing on comparing the benefits of a land rent with various rental systems. This Rice Field Rental Application has four main features, namely Registration of Lease Members and List of FarmLand that is ready to lease, Lease and Payment Transactions (Direct Lease or with Intermediary Services), Preparation and Verification of Rice Field Rental Agreements, and Preparation of Final Reports of Rice Field Rental. The results of Alpha testing using BlackBox testing show that all functionalities are running successfully according to the test scenario. While beta testing to users shows that 86.3% of users can accept this Rice Field Rental Application. Keywords: Application, Online Rental, Farmland, Alpha/Beta Testing.